Medium Chain and Long Chain Alkanes Hydroxylase Producing Whole Cell Biocatalyst From Marine Bacteria - Thontowi, Ahmad; Yetti, Elvi; Yopi, Yopi (ANNALES BOGORIENSES, 2018)
Alkanes areÂ  major component of crude oil that could be hydrolyzed by the enzyme of alkane hydroxylase. The are three types of alkane hydroxylase based on the chain length of alkane such as short-chain length/SCL (C2-C4), medium-chain length/MCL (C5-C17), and long-chain length/LCL (C>18). The aims of this study were to characterize and identify alkanes-degrading bacteria from these bacteria. The 30 strains from marine were grown on MCL (Pentane-C5H12, Decane-C10H22, and Pentadecane-C15H32) and LCL (n-Paraffin-C12H19C17 and branch of Pristane-C19H40). The study showed twenty-nine isolates have the ability to degrade alkanes compounds, whereas 14 isolates have grown ability on MCL and LCL medium, 11 isolates have the ability to grow on MCL and n-LCL, 3 isolates have the ability only to grow on MCL medium and 1 isolate has the ability only grow on n-LCL medium. The growth test result indicated that 29 isolates have medium-chain alkane monooxygenase and long-chain alkane hydroxylase. Based on 16S rDNA gene analysis, we obtained twenty nine of oil- degrading bacteria, namely a-proteobacteria (57 %), g-proteobacteria (30 %), Flavobacteria (7 %), Bacilli (3%) and Propionibacteriales (3 %). g-Proteobacteria and a-proteobacteria which seems to play an important role in the alkane biodegradation.